The clinical application of plasma Kaposi sarcoma herpesvirus viral load as a tumour biomarker: results from 704 patients. Issue 1 (25th June 2015) - Haq, I‐U; Dalla Pria, A; Papanastasopoulos, P; Stegmann, K; Bradshaw, D; Nelson, M; Bower, M
Abstract : Objectives: The aim of the study was to evaluate the role of plasma Kaposi sarcoma herpesvirus (KSHV) as a diagnostic and prognostic biomarker in people living with HIV (PLWH) and diagnosed with KSHV‐associated diseases. Methods: Using quantitative nested polymerase chain reaction (PCR) targeting the open reading frame‐26 gene of KSHV, plasma levels of KSHV were measured in consecutive PLWH with KSHV‐associated diseases or as part of the investigation of lymphadenopathy. Results: Plasma KSHV assays were performed on samples from 684 PLWH and 20 HIV‐seronegative people with KSHV‐associated malignancies. In PLWH, plasma KSHV was detected in 39% of those with KS, 99% of those with multicentric Castleman disease (MCD), 9% of those with non‐Hodgkin lymphoma (NHL), 2% of those with non‐AIDS‐defining malignancies and 0% of those with nonmalignant lymphadenopathy. There was no significant difference in plasma KSHV viral load among those with KS, MCD and KSHV‐associated NHL. The 5‐year overall survival rate from KS diagnosis of 335 PLWH was 95.2% (95% confidence interval 92.6–97.8%). Plasma KSHV viraemia did not predict overall survival in those with KS ( P = 0.73), nor when those with T0 stage KS ( P = 0.52) or T1 stage KS ( P = 0.62) were analysed separately. Conclusions: Measuring the plasma levels of KSHV as a biomarker in KSHV‐associated disease has a very limited value in either diagnosis or prognostication. The only potential role of clinical value is the suggestion that an undetectable plasma KSHV excludes a diagnosis of MCD in PLWH.